Massive lower gastrointestinal bleeding after low anterior resection for middle rectal cancer – case report - Mircea Beuran; Ionut Negoi; Sorin Paun; Valentina Negoita; Bogdan Stoica; Ioan Tanase; Mihaela Vartic; Ruxandra Irina Negoi; Sorin Hostiuc (Journal of Acute Disease, 2015)
Objective: To emphasize the value of emergency diagnostic angiography and angioembolization in massive postoperative bleeding. Methods: A case report was presented and electronic search of U.S. National Library of Medicine National Institutes of Health PubMed/MEDLINE, EMBASE, Google Scholar, ISI Web of Knowledge, to identify original articles and reviews about the subject. Results: A 55 year-old male patient was addmited for rectal bleeding. ECOG index=2, digital rectal examination revealed the inferior pole of a middle rectal tumor. Colonoscopy exam validated the presence of a middle rectal tumor, 8 cm from the anal verge. CT scan showed rectal wall thickening up to 3 cm, that extends 9 cm proximally, whit infiltration of the perirectal fatty tissue and multiple enlarged lymph nodes up to 12 mm in dimension. There was a laparoscopic converted to open approach, with low anterior resection of the rectum and total mesorectal excision, an end to end stapled colorectal anastomosis and protective loop ileostomy. In the 5th postoperative day a massive lower gastrointestinal bleeding occured, with hypovolemic shock and a decrease in hemoglobin. Emergency angiography was performed. This revealed active bleeding from an internal iliac branch that was successfully angioembolized. Conclusions: Angiography with angioembolization is an effective tool in emergency setting, avoiding the morbidity and associated mortality of a surgical reinervention. In early postoperative hemorrhages, only a rapid clinical recognition, a personalized diagnostic workup and an agressive intervention may offer the patient the best chances for cure.